TESTS OF DIFFERENT TYPES OF IMPLANTS FOR CARDIAC SUPPORT DEVICE. MORPHOLOGICAL RESEARCH DATA - A. V. Timerbaev; I. V. Dmitriev; E. K. Gasanov; I. M. Iljinsky; S. N. Shyrigin; D. V. Shumakov (Вестник трансплантологии и искусственных органов, 2010)
Morphological research of canine cardiac tissues after implantation several types of implants has been made. The first group consisted of animals with implanted «Eslan+Elasto-POB» implants, the second was after im- plantation of «Eslan» implants, and the third group after «Ftorex» implants. Fabrics were implanted on canine heart muscular tissue. Muscular tissue with implant were examined by light microscopy. There were no early or late deaths of animals, no infectious complications in any groups and terms. The reactions in muscular tissue in response to implantation of implants were defined as typical pathological processes and manifested by alterative, exudative reactions with edema, ill-defined hydropic degeneration and formation of inflammatory infiltration in the early terms (20 days). The formation of mature granulation tissue was accompanied its invasion between pores of implants and giant-cell reaction (20 days). After that thin layer of connective tissue was formed at the periphery of implant (30 and 60 days). Development of ill defined fibrosis was revealed in late postoperative terms at the circumference of implant (30 days – 60 days). There were no substantial differences in features of tissue’s responses to implantation of all types of implants.